Phytochemical profile and pharmacological activities of hemigraphis colorata: a review - S, Tejaswini K; T L, Harsha; C B, Hamsa; S S, Nischith; M, Rupesh Kumar; D R, Bharathi; Syed, Sagheer Ahmed (International Journal of Indigenous Herbs and Drugs, 2022)
The use of herbal plants in the medical system plays an important role in the treatment of illnesses. Researchers all over the globe are exploiting the medicinal plants because of their least side effects, high efficacy and safety. Advancement in science technology has led to the development of a novel formulation from the medicinal plants. Exploitation of such medicinal plants has helped in treatment of ailments and it management. Even though researchers are discovering the hidden potentials of the medicinal plants still there are many underutilized medicinal plant with potent remedies. Amoung such plants Hemigraphis colorata is a plant that has significant part in the medicine system and has made a remarkable impact in traditional medicine treatment. The plant has been used in treatment of bloody dysentery, bacterial infection, fungal infection, haemorrhoids and as a wound healing agent. Along with these several pharmacological studies also suggest that the plant has potent antibacterial activity, anti-inflammatory activity, anticancer activity, antidiabetic activity, antidiarrheal activity etc. these activities can be a results of its vast phytochemical composition which includes alkaloids, tannins, glycosides, steroids, flavonoids etc. the present review is an effort made to collect all the available information regarding the phytochemistry, traditional usage and pharmacological activities.